Implementation of Pancasila Values in the Formation of Law No. 1 of 2023 (New Criminal Code) - Harahap, Ahmad Rivai Ardiansyah; Farros, Sayyid Al; Hosnah, Asmak Ul (PT FORMOSA CENDEKIA GLOBAL, 2025)
The historical journey of the Indonesian nation from the colonial era to independence can be understood as a paradigmatic journey. Politically, Indonesia underwent a transformation from a peripheral nation to an entity that took over the center of power through the proclamation of independence in August 1945, moving from the Dutch East Indies to the Republic of Indonesia. Not all nations that have achieved independence have tried to build a new life based on innovative principles. In this context, the role of Pancasila and the 1945 Constitution (1945 Constitution) has a very important significance to these fundamental changes. Pancasila, as a basic state norm (staatssfundamentalnorm), functions as a grand design for society and a new life in Indonesia. Similarly, the establishment of Law Number 1 of 2023 concerning the National Criminal Code (KUHP) still reflects the values of Pancasila as the country's basic norm which will come into effect in 2026. Law Number 1 of 2023 (New Criminal Code) introduces a number of new criminal concepts that are different from the previous Criminal Code. This renewal is expected to be able to answer the legal challenges faced today and replace colonial concepts that have become obsolete and no longer relevant in overcoming contemporary problems. This update covers three main issues in criminal law: first, the formulation of unlawful acts; second, criminal liability, both against individuals as perpetrators and against legal entities; and third, the type of crime and actions that can be applied. The change in the concept of penal in the National Criminal Code is influenced by the development of criminal theory, which shows a shift from a retributive approach to restorative justice. Therefore, the purpose of criminalization is not only to focus on punishment, but also to try to balance two aspects of community protection, namely the victim and the perpetrator.